New variants of the Schroder method for finding zeros of nonlinear equations having unknown multiplicity - Thukral, R. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
There are two aims of this paper, firstly, we define new variants of the Schroder method for finding zeros of nonlinear equations having unknown multiplicity and secondly, we introduce a new formula for approximating multiplicity m. Using the new formula, the five particular well-established methods are identical to the classical Schroder method. In terms of computational cost the new iterative method requires three evaluations of functions per iteration. It is proved that the each of the methods has a convergence of order two. Numerical examples are given to demonstrate the performance of the methods with and without multiplicity m.